Brewed awakening [large type] - Coyle, Cleo (Coyle, Cleo. Coffeehouse mystery, 2020)
"When coffeehouse manager Clare Cosi awakens on a bench in Washington Square Park, she has no idea she's been missing for the past week, or that her friends and family have been frantic with worry. Now that she's back, everyone is overjoyed, including a handsome NYPD detective who claims to be her fiance. But to Mike Quinn's crushing distress, Clare doesn't remember him, or much of anything about the last decade of her life. Clare's missing memory is tied to a crime she witnessed. An acquaintance of Clare's elegant employer-and fellow member of an exclusive Gotham circle known as " The Ladies Who Brunch "-invited Clare to her posh hotel to sample gourmet wedding cakes. The pair took a stroll after their indulgent tasting and, according to security camera footage, a masked figure snatched the hotel heiress at gunpoint with Clare looking on. Did the kidnapper take Clare, too? The camera went dark, just like Clare's memory. Soon authorities grow suspicious. Is Clare really a victim? Or merely acting like one? Evidence is mounting that she set the woman up. To clear her name, Clare must find a way to reclaim her memories and rescue the heiress before this high-stakes crime ends in tragedy. Otherwise, instead of walking down the aisle, Clare may find herself perp-walking to prison as an accomplice to kidnapping and murder"--